ANALISIS VARIASI KEMIRINGAN SUDUT TURBIN SINGLE BLADE TERHADAP EFISIENSI DAN DAYA PADA ARCHIMEDES SCREW MENGGUNAKAN COMPUTIONAL FLUID DYNAMICS (CFD) - Ahmad, shofiyuddin Ali; Fajarningrum, Nurmala Dyah; Iswahyudi, Sigit (ELEMEN : JURNAL TEKNIK MESIN, 2024)
The potential for renewable energy in Indonesia is abundant, such as water energy. This energy potential can be used for Micro Hydro Power Plants (PLTMH). This study aims to study the effect of turbine head angle and screw angle parameters on the efficiency and power of screw-type water turbines. The angles used are turbine shaft angles of 20 °, 25 °, and 30 ° at screw angles of 22 ° and 26 °. Then a design was made using Autodesk Inventor and then simulated using Ansys software. The results of the study showed that the greatest power and the greatest turbine efficiency were obtained at a screw angle of 26 ° with a turbine shaft angle of 30 ° with a power value of 80072.98 watts and an efficiency of 95.37%. While the lowest power and efficiency were at a screw angle of 22 ° and a shaft angle of 20 ° with a power value of 72643.44 watts with an efficiency of 86.52%. So from this research, it was found that the good angle value is at the variation of the thread angle of 26° and the turbine shaft angle of 30°.